Intraspecific diversity in Sinningia speciosa (Gesneriaceae: Sinningieae), and possible origins of the cultivated florist's gloxinia - Zaitlin, David (Oxford University Press, 2012)
BACKGROUND AND AIMS: The florist's gloxinia is a familiar houseplant in the Gesneriaceae, the botanical family that includes the African violet (Saintpaulia) and other ornamental species. The gloxinia's wild progenitor is Sinningia speciosa (Lodd.) Hiern, a Brazilian endemic. Although it has been cultivated for almost 200 years, little is known about the genetic diversity in S. speciosa, how the wild populations relate to one another or even where the cultivated forms originated. Using available wild collections, preliminary phenetic and phylogenetic investigations were conducted to elucidate the interspecific relationships within S. speciosa and to infer the origins of the cultivars. METHODOLOGY: Amplified fragment length polymorphism (AFLP) analysis was applied to 24 accessions of S. speciosa (17 wild collections, seven cultivars) and one accession each of Sinningia guttata and Sinningia macrophylla. A maximum likelihood (ML) tree was also calculated from an alignment of the nuclear ribosomal internal transcribed spacer sequence from the same 26 accessions. PRINCIPAL RESULTS: Dice/UPGMA and principal coordinates analysis of the AFLP data partitioned S. speciosa into several distinct clusters, one of which included S. macrophylla. All cultivated ‘gloxinias’ grouped together in a major cluster with plants from Rio de Janeiro. The AFLP results were compared with a phylogenetic analysis of the ribosomal spacer region, which was informative in S. speciosa. The ML tree generally supported the AFLP results, although several clades lacked strong statistical support. CONCLUSIONS: Independent analyses of two different data sets show that S. speciosa is a diverse species comprised of several lineages. Genetic distance estimates calculated from the AFLP data were positively correlated with geographic distances between populations, indicating that reproductive isolation could be driving speciation in this taxon. Molecular markers are under development for population genetic studies in S. speciosa, which will make it possible to define evolutionarily significant units for purposes of conservation.